POLA ASUH ORANGTUA DALAM MEMBENTUK PERILAKU MORAL PADA ANAK REMAJA (Studi Kasus Pelajar di SMA Negeri Tuah Kemuning Kecamatan Kemuning Kabupaten Indragiri Hilir) - Yupit Yuliyanti; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Family is the first and foremost place for children to get education. Psychic satisfaction acquired by the child in the family will greatly determine how their behavior in the environment. Parenting parent in shaping morality behavior in children in Senior High School Tuah Kemuning District Indragiri Hilir is democratic, permissive and authoitative. Morality Behavior of children in SMA Negeri Tuah Kemuning Sub-district Indragiri Hilir Regency is still low there is the some number of cases on Teenage Delinquency problem recently, which observed their behavior in bringing HP to school even though it is prohibited, The parent ignorance to problems that happened to their children, especially his personal problems and lack of parental attention to their childrens education. The purpose of this research is to know the parenting parent of democracy, permissive and authoritative influence to moral behavior in adolescent (Case Study of Student in Senior High School of Tuah Kemuning Kemuning Sub-district Indragiri Hilir Regency).The methods that use in this study is correlational quantitative method research, conducted in SMA Negeri Tuah Kemuning District Indragiri Hilir Regency, with the number of samples 35 respondents encountered in the field with incidental sampling technique. In the data collecting researchers using a questionnaire technique. The results of this study indicate that parenting (democratic, pemisisif, authoritarian) has a positive effect on morality formation of students in SMA Negeri Tuah Kemuning Kemuning Sub-district Indragiri Hilir Regency. Keywords; Parenting parent, Morality